La desnutrición y su influencia en el desempeño escolar en estudiantes de la Unidad Educativa Nahim Isaias Barquet Las Marías – Baba – Los Ríos durante el periodo octubre 2018 – abril 2019 - Castro Vieira, Hector Kevin (2019)
INTRODUCTION: "The problem of chronic malnutrition in school-age children is a serious problem in the country", as it causes them "a permanent alteration" to their physical and motor development, radically influencing their learning process 22.6% of Ecuadorian children suffer from malnutrition according to a study carried out this year. Despite being high, the percentage is 3.4 percentage points lower than in 2006, when the child population of school age with chronic malnutrition was 26 percent. OBJECTIVE: To identify the relationship between malnutrition and school performance of the students of the NAHIM Educational Unit ISAIAS BARQUET Las Marías - Baba - Los Ríos. METHODOLOGY: In the present research project, the inductive logical method has been used where particular facts that have been evidenced in the course of the investigation have been taken, taking as a reference the previously hypothesized hypothesis that will allow to affirm or refute the aforementioned hypothesis. RESULTS:It was shown that the academic achievement levels cover a large percentage where the most predominant was a bad academic performance with 62% (10), and in relation to the BMI 35% 6 find moderate malnutrition and 29% 5 He is severely malnourished, which indicates that students who show degrees of malnutrition are those in which low academic performance is evident. CONCLUSION:When carrying out the inferential analysis, statistically significant results were obtained, which allowed accepting the research hypothesis